THE IMAGE OF THE RUSSIAN WORKER IN THE SYSTEM OF PERSONNEL MANAGEMENT: CULTURAL AND GENDER ASPECTS - Grachev , A. A. (Modern Psychology, 2019)
The article discusses the problem of the image of the employee included in the personnel management system. It is shown that an adequate image of the employee, the core of which are the motivational characteristics, allows you to build an effective system of motivation, focused on the satisfaction of his vital interests. The basis for determining the set of motivational characteristics of the employee was a three-component model of life orientations, involving a deficit orientation, orientation to self-realization and spiritual. The empirical study identified typical images of a typical and ideal Russian worker for adult working people and students. The connection of these images with the Russian national culture is shown: in images of typical and ideal workers orientation on the relations, on communication, on mutual aid is expressed. The gender features of the employee's images associated with the fact that women seem to be more relationshiporiented than men are determined.
Keywords: image of the employee, life orientations of the employee, typical employee, ideal employee, cultural features of the image, gender features of the image